Feminism in Islam: Its Relation to the Rights and Responsibilities of Career Women in Domestic Spaces - wahyu, wahyu; Suwandi, Suwandi; Rofiq, Aunur (UIN Sunan Gunung Djati Bandung, 2023)
This study investigates the intersection between feminism in the context of Islam and its influence on the rights and obligations of career women in the domestic environment. Employing an explanatory approach, the study aims to examine the causal relationship between the understanding of feminism in Islam and the dynamics of rights and obligations within family structures. Data were collected through interviews with relevant respondents and an extensive literature review. The findings indicate that feminist thought in Islam emphasizes equality in rights and obligations between women and men across various aspects of life, including in the context of women's careers. This research also examines the fair distribution of domestic duties and the concept of an ideal family in Islam, reflecting equality for both partners. This study is particularly relevant amidst the evolving roles of women in society, especially those who are career-oriented. By providing a thorough analysis, this research strives to highlight how feminism in Islam can influence the rights and obligations of career women in the domestic sphere, and underscores the need for a harmonious balance between religious teachings and aspirations for gender equality. The contribution of this research lies in developing an inclusive perspective on the role of women in Islamic society.